Implementasi Metode Full Time Equivalent (FTE) Dalam Analisis Kebutuhan Tenaga Kerja - Eka Rakhmat Kabul; Mohammad Nouval Febrianto (IKRAITH-EKONOMIKA, 2022)
Analysis of manpower needs is part of human resource planning. traditionally, human resource planning isan activity in human resource management used by organizations to ensure that they have the right amountand type of human resources, thereby growing certainty that they carry out the work at the right place andtime to meet business objectives. With good human resource planning, companies can avoid employeevacancies, both now and in the future. This study will discuss the measurement of employee workload withthe full time equivalent method. the research was conducted on a case study in one of the largest PVCproducing companies in indonesia, which is located in DKI Jakarta. the results showed that the workloadborne by the employees in the workshop department was 35% or 10 employees had a low/underloadedworkload, 45% or 13 employees had a normal/fit workload, and 20% or 6 employees had a high/overloadedworkload. meanwhile, the optimal number of workforce needs in the workshop department is 27 employees.Optimizing employee performance can be done by changing the composition of the number of workersaccording to the calculation of the optimal number of workers and rearranging the job description.